2008
DOI: 10.1016/j.jvs.2008.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of calcification and intraluminal thrombus on the computed wall stresses of abdominal aortic aneurysm

Abstract: The presence of calcification increases AAA peak wall stress, suggesting that calcification decrease the biomechanical stability of AAA. In contrast, intraluminal thrombus reduces the maximum stress in AAA. Calcification and intraluminal thrombus should both be considered in the evaluation of wall stress for risk assessment of AAA rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
137
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(148 citation statements)
references
References 47 publications
9
137
1
1
Order By: Relevance
“…It may well result from the formation of ILT at the previous "shoulder area," which tends to reduce the stress in the AAA. 10 Although no concomitant increase from baseline for the overall stress, overall maximum diameter stress, and overall shoulder stress was observed, a positive correlation between the expansion rate and the shoulder stress was identified. Further analysis of the 2 groups revealed that this relationship exists for rapidly expanding aneurysms only and not for slowly expanding aneurysms.…”
Section: Et Al Shoulder Stress and Aneurysm Growthmentioning
confidence: 82%
See 1 more Smart Citation
“…It may well result from the formation of ILT at the previous "shoulder area," which tends to reduce the stress in the AAA. 10 Although no concomitant increase from baseline for the overall stress, overall maximum diameter stress, and overall shoulder stress was observed, a positive correlation between the expansion rate and the shoulder stress was identified. Further analysis of the 2 groups revealed that this relationship exists for rapidly expanding aneurysms only and not for slowly expanding aneurysms.…”
Section: Et Al Shoulder Stress and Aneurysm Growthmentioning
confidence: 82%
“…9,10 A patientspecific study previously demonstrated that maximum wall stress was 12% more specific and 13% more sensitive in predicting AAA rupture than maximum diameter alone. 11 In other patient-specific studies, peak stress was found to be significantly higher in ruptured AAAs than nonruptured AAAs.…”
Section: Clinical Perspective On P 1822mentioning
confidence: 99%
“…The ratio of the vessel stress to vessel strength is regarded as an alternative tool to conventional diameter criteria, which may be insufficient in small aneurysms. In computational simulations, vessel stress is calculated as a function of the vessel diameter [7,34], wall thickness [36,37], asymmetry [14,18,34,36], tortuosity [21], material property [17,24,29,38], calcification [15,22], intraluminal thrombus (ILT) [5,15,16,33], and blood flow [4, 9, 13, 14, 17, 20, 25, 26, 28-30, 32, 35-41]. Blood vessel strength is measured by ex vivo studies [11,12,23,31,44] or estimated by effective features such as ILT existence, sex, and genetic vulnerability [10].…”
mentioning
confidence: 99%
“…Although, there is a lack of agreement on how calcifications actually affect it. Since the discussed constituent is stiffer than the rest of the wall, it presents possible stress concentration which is consistent with higher rupture probability [32,33]. On the other hand, calcifications cause local wall thickening [11] and demonstrate significant loadbearing effects, which results in lowering the wall stress [34].…”
Section: Presence Of Intraluminal Thrombus and Calcifications In Aaa mentioning
confidence: 77%